2016
DOI: 10.1016/j.jsbmb.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D inhibits glutamine metabolism in Harvey-ras transformed MCF10A human breast epithelial cell

Abstract: Breast cancer is the second most common cancer among women in the US. The active form of vitamin D, 1,25-dihydroxyvitamin D (1,25(OH)2D), is proposed to inhibit cellular processes and to prevent breast cancer. The current studies investigated the effect of 1,25(OH)2D on glutamine metabolism during cancer progression employing Harvey-ras oncogene transformed MCF10A human breast epithelial cells (MCF10A-ras). Treatment with 1,25(OH)2D significantly reduced intracellular glutamine and glutamate levels measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…We observed a slight increase in intracellular lactate concentration in vitamin D-treated cells (Fig. 2 , Table S2 ), corroborating the subtle effect of vitamin D on glycolysis, which was already described for other cell models 10 , 11 , 31 . To better understand this effect, we measured the fate of glucose carbons by incubating HEK293T cells with 13 C-glucose and measuring 13 C-lactate accumulation in the culture medium.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…We observed a slight increase in intracellular lactate concentration in vitamin D-treated cells (Fig. 2 , Table S2 ), corroborating the subtle effect of vitamin D on glycolysis, which was already described for other cell models 10 , 11 , 31 . To better understand this effect, we measured the fate of glucose carbons by incubating HEK293T cells with 13 C-glucose and measuring 13 C-lactate accumulation in the culture medium.…”
Section: Resultssupporting
confidence: 88%
“…It has been shown that vitamin D treatment inhibits glycolytic flux in metastatic ras transformed MCF10A cells, as shown by a decrease in 3-phosphoglycerate and lactate contents and a reduced activity of lactate dehydrogenase 10 . In the same cells, vitamin D inhibits glutamine metabolism, reducing glutamate and glutamine intracellular contents 11 . Additionally, vitamin D treatment increased insulin secretion in polycystic ovary syndrome (PCOS) patients 12 , and suppressed the expression of angiotensinogen induced by hyperglycemia by blocking NF-kB-mediated pathway 13 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the metabolic homeostasis of individuals with oncogenic germline mutations (RASopathies) remains unclear. Recent studies have shown that cancer cells with RAS mutations exhibit altered metabolism characterized by enhanced glucose uptake, glycolysis, lipid synthesis and glutamine catabolism ( Bryant et al, 2014 , Zheng et al, 2015 , Zhou et al, 2016 ). To gain an understanding of the effects of RAS activation on energy homeostasis in vivo , we generated knock-in mice expressing the Costello syndrome-associated Hras G12S mutation and examined energy homoeostasis in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of MCF10A- ras cells with 1,25(OH) 2 D resulted in decreased glucose metabolism in the glycolytic pathway as well as its flux into the TCA cycle [20]. Additionally, 1,25(OH) 2 D inhibited glutamine uptake and its downstream flux into the TCA cycle in both MCF10A- ras and MCF10A HER2/neu (MCF10A- ErbB2 ) overexpressing cells, the latter being one of the most commonly amplified genes in breast cancer [22,23]. Given the importance of glucose and glutamine metabolism in redox balance, and the effect of 1,25(OH) 2 D on both of these pathways, the purpose of the following studies was to investigate the effect of 1,25(OH) 2 D on endogenous antioxidant defenses in early stages of breast cancer.…”
Section: Introductionmentioning
confidence: 99%